Implementasi Media Periklanan Pada Horison Bogor Icon Hotel - Jaya, Pinto; Febrianti, Sisca; Mulyana, Mumuh; Zuhdi, Saefudin (Program Vokasi dan LPPM IBI Kesatuan, 2023)
ABSTRACTWith the development of the tourism industry sector in tandem with the hospitality industry in Indonesia, this will affect the number of star hotels that are widespread in Indonesia. With so many hotels spread across Indonesia, this has an effect on hotel competition with other competitors. Therefore, these hotel companies must carry out good promotions, one of which is by advertising as a promotional medium to customers by providing information regarding the products and services offered. The purpose of the research conducted by the author is to find out what types of advertising media are used to promote products and services at the Horison Bogor Icon Hotel, what are the obstacles in using the types of advertising media used at the Horison Bogor Icon Hotel, how to deal with obstacles from types of Advertising Media used by Horison Bogor Icon Hotel, This research was conducted by the author at the Horison Bogor Icon Hotel which is located in Bukit Cimanggu City, Jl Sholeh Iskandar No. 1 , RT , 01/RW, 13, Cibadak, Tanah Sereal, Bogor City. Held for 6 months from December 2021 to June 2022. Through this research the authors get the result that the Horison Bogor Icon Hotel. Using several types of Advertising Media used by the Horison Bogor Icon Hotel in promoting its products and services, including: print media by choosing brochures and billboards as advertising media, electronic media by choosing Radio as an advertising medium, Digital Advertising by choosing Social Media which focuses on on Instagram as an advertising medium and the Website as an advertising and information medium, SEM (Search Engine Marketing) as an advertising medium. Constraints from the type of advertising media used by the Horison Bogor Icon Hotel, namely in the use of electronic media by choosing radio that has a small audience of radio listeners that are rarely used by the public as well as SEM or Search Engine Marketing which has obstacles in it, namely the large number of incoming information and words the search keys on Google tend to be the same, this allows other people who are looking for information related to the Horison Bogor Icon Hotel to enter the wrong website page to another website. Apart from that, the Algorithm changes on Google, which are updated almost 600 times a year, which can affect marketing.